Durability design of concrete structures in severe environments - Gjørv, Odd E. (Taylor & Francis, 2009)
By designing in corrosion prevention and through preventive maintenance, you can substantially reduce the overall service cost of a concrete structure. Taking a probabilistic approach to the engineering design issues, this book tackles the challenge of controlling durability and service life of concrete structures in severe environments. Many durability problems are caused by poor quality control as well as special problems during concrete construction. You must firmly grasp the issue of construction quality and variability before you can successfully control durability. This book helps by giving: reviews of field performance, deteriorating processes and current codes and practice; methods for calculation of corrosion probability; performance-based concrete quality control; corrosion prevention and preventive maintenance; calculation of life cycle costs and life cycle assessment; and, recommended job specifications. Internationally relevant with a practical focus, this is the essential guide for consulting and construction engineers involved in the design and execution of new concrete structures.